Aptera : the future of financing (C) - Fleming, Lee, active 2022; Sorenson, Olav (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2022)
Aptera is on its second life. It originally began as a VC-backed electric car company in the 1990s. But that first life ended badly, as the company could not raise enough money to keep going in the wake of the financial crisis (covered in the A case). The original founders have resurrected the company with a new, more capital efficient, approach to production (reviewed in the B case) and a solar panel powered design. To finance the venture, they have been considering using some of the new provisions available for equity crowdfunding, including Reg CF and Reg A+, instead of going the VC route (discussed in the C case).The case has been developed to cover a variety of issues. One important pasture of discussion is strategy and operations. A second is how the company plans to finance their venture. For both questions, the first life of the company importantly influences how the founders think about these issues. In this note, we detail how one could address all these issues in an 80- to 90-minute class. However, both the strategy and operations and the financing raise a rich enough set of questions that a 60- to 80-minute class could focus on just one of them.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Aptera Motors -- Case studies; Electric automobiles -- Economic aspects -- Case studies; Automobile industry and trade -- Finance -- Case studies